Etiological factors and treatment of chylothorax in paediatric patients - a systematic review - Knop, Kinga; Kochanowska, Anna; Piasecka, Zuzanna; Kosieradzka, Karolina; Drozd, Małgorzata; Bodajko-Grochowska, Anna (Journal of Education, Health and Sport, 2022)
Chylothorax is an accumulation of chyle in the pleural cavity. It is a relatively rare cause of pleural effusion in children and its annual incidence is 14 cases per 100 000 children in Europe. The pleural fluid triglyceride level greater than 110 mg/dl with a cholesterol level lower than 200 mg/dl confirms the diagnosis of chylothorax. Medical imaging are also necessary such as a non-invasive and easily accessible lung ultrasound. Symptoms of this disease are tachypnea, dyspnea, and in some cases dry cough. This review aims to summarize the current literature regarding chylothorax in children, analyze its possible etiologies and treatments. The causes of chylothorax are varied. It may appear after surgical interventions, traumas, infections and also be congenital. Iatrogenic factors are the most common cause of chylothorax in children with cardiothoracic surgeries. Management of chylothorax can be quite complex and highly variable, depending on patient’s condition and their response to the introduced treatment. Conservative treatment consisting of nutrition therapy, chest drain, and pharmacotherapy is typically a first-line of treatment. Diet modification consist in dietary supplements enriched with medium chain triglycerides (MCT) or starting the patient on a total parenteral nutrition (TPN). In most of the analyzed cases the conservative treatment alone proved sufficient in the management of chylothorax. In case of its failure, surgical treatment was a secondary therapy choice. One of the most common surgical procedures for pleural effusion is a thoracic duct ligation (TDL) or pleurodesis and both of these methods are highly effective therapy for chylothorax. This review of the literature reveals a wide variety of causes and methods of treatment of chylothorax. There are no clear standards of management and the therapy is adjusted to the clinical condition of the patient.